Protective mechanisms of resveratrol derivatives against TNF-α-induced inflammatory responses in rat mesangial cells. (January 2019) - Lee, I-Ta; Lin, Chwan-Fwu; Huang, Yu-Ling; Chong, Kowit-Yu; Hsieh, Ming-Fa; Huang, Tse-Hung; Cheng, Ching-Yi
Graphical abstract: Highlights: TNF-α enhances PGE2 generation via cPLA2 /COX-2 upregulation in RMCs. Resveratrol derivatives have the anti-inflammatory effect on TNF-α-treated RMCs. Resveratrol derivatives inhibit TNF-α-induced COX-2 expression via MAPKs. Resveratrol derivatives attenuate TNF-α-induced NF-κB activation. Abstract: Introduction: Resveratrol has been reported to alleviate inflammatory responses and oxidative stress in mesangial cells and in several types of renal injury in animal models. Previously, the active resveratrol derivatives from the roots of Vitis thunbergii Sieb. & Zucc. (Vitaceae) were shown to have significant anti-platelet and anti-oxidative activities. However, the anti-inflammatory mechanisms of these resveratrol derivatives in rat mesangial cells (RMCs) have not been clarified fully. Methods: The protective mechanisms of resveratrol derivatives involved in tumor necrosis factor-α (TNF-α)-induced inflammatory responses were assessed by Western blot analysis, real-time PCR, and RT–PCR. The involvement of various signaling molecules in these responses was investigated using selective pharmacological inhibitors. Results: Nontoxic concentrations of the resveratrol derivatives significantly attenuated cytosolic phospholipase A2 (cPLA2 ) and cyclooxygenase 2 (COX-2) expression in RMCs challenged by TNF-α. These resveratrol derivatives inhibited TNF-α-activated ERK1/2 and JNK1/2 without affecting p38 phosphorylation. Next, we demonstrated that TNF-α induced NF-κB activation, translocation, and promoter activity, which was inhibited by pretreatment with resveratrol derivatives in RMCs. Conclusion: The protective mechanisms of resveratrol derivatives against TNF-α-stimulated inflammatory responses via cPLA2 /COX-2/PGE2 inhibition was caused by the attenuation of the JNK1/2, ERK1/2, and NF-κB signaling pathways in RMCs.